European regulation of the cryptocurrency market and implementation in Ukraine - Dotsenko, Oleksii; Mykhnia, Alona (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2023)
The world economy is at the initial stage of introducing modern digital technologies. Currently, there is also a permanent process of awareness by the world community of the fact that the digital economy, special finance and Internet trade will have a decisive importance on a global scale in the future. Therefore, the article is devoted to the study of the international practice of legal regulation of cryptocurrency circulation with an analysis of the current situation in Ukraine. The relevance of this direction of research is determined not only by the spread of popularity of virtual currencies, but also by the recent adoption of the European MiSA regulation, which was taken as a basis for the specialized Law. It was established that our state has prospects for the development of a competitive market, which in turn has a positive perspective for the development of the economy under martial law.